Kajian Etnokoreologi Tari Krincing Jagat di Sanggar Seni Way Talatah Subang - Maryani, Dian; Narawati, Tati; Badaruddin, Saian (Universitas Negeri Medan, 2025)
Krincing Jagat Dance is a new form of creative dance inspired by the traditional art of Sisingaan from Subang, West Java. This dance was created by Sigit Febrianto at Sanggar Waytalatah Subang as an effort to preserve local culture with an innovative touch to remain relevant amidst the development of the times. This study aims to describe the text and context of Krincing JagatDance through ethnochoreology studies. Textually, Krincing Jagat Dance combines elements of movement, music, and dance properties such as krincing (small bells) to form a dynamic and expressive dance composition. There are 22 movements that can be divided into 3 parts of movement composition, namely gesture, locomotor and pure movement. This study uses an Ethnochoreology approach which is used as a Grand theory, using a descriptive analysis method and using a qualitative paradigm. Data were obtained through direct observation at the Waytalatah Art Studio, interviews with the dance creators, and documentation of the Krincing JagatDance. The results of the study indicate that the Krincing JagatDance not only maintains the aesthetic values ​​of the Sisingaan tradition, but also brings a new spirit through freer and rhythmic choreography, without leaving behind local identity.